The Relationship Between the Type of Mother's Work and the Development of Preschool-Aged Children in RA Azzahro, Kencong District Jember 2022 - sutrisni, sutrisni; Putri Wahyu Wigati; Halimatus Saidah (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
Mother's employment status is one of the factors that influence the occurrence of developmental disorders in children. The results of a preliminary survey conducted in May 2022, on 10 preschool children experiencing language development disorders 2 (20%), psychosocial development disorders 4 (40%) preschool age children, the purpose of this study was to determine the relationship between mother's employment status and child development at age preschool children at RA Azzahro, Kencong District, Jember Regency in 2022. This study uses research methods Analytical Correlation. In this research, sampling techniques or sampling technique used is the technique of the total sample (total sampling). This study was conducted on 42 respondents parents and pre-school children. The results showed that based on the results of the Chi Square test with a significant level of 0.05, p value = 0.009 = 0.05 then H0 was rejected and H1 was accepted, which means that there is a relationship between the mother's work status and child development while the value (r ) = 0.538 shows that the relationship between mother's work status and child development has a moderate correlation with a positive direction, which means that the better the mother's job status, the better the development of children in RA Azzahro, Kencong District, Jember Regency in 2022. Lack of stimulation given to children can cause developmental disorders such as children not trained for balance, then the child will have difficulty in moving so physically untrained child.